Interpersonal violence in the state of Espírito Santo: analysis of mandatory notifications between 2011 and 2018 - Franciéle Marabotti Costa Leite; Luíza Eduarda Portes Ribeiro; Tiffani Matos Oliveira; Evellym Souza Correa; Márcia Regina de Oliveira Pedroso; Dherik Fraga Santos (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To identify the frequency of notifications of interpersonal violence in Espírito Santo from 2011 to 2018, and the factors associated with this issue. Methods: This is a cross-sectional study in which all cases of interpersonal violence from the Information System for Notifiable Diseases in the state of Espírito Santo during the period from 2011 to 2018 were analyzed. Absolute and relative frequencies and 95% confidence intervals were calculated, as well as Poisson regression. Results: During the analyzed period, 27,277 cases were reported in Espírito Santo (P: 75%; 95% CI: 74.5-75.4), being more prevalent among females, children, and the elderly, individuals of black/mixed race, people without disabilities, and residents of urban areas. Regarding the perpetrator, there was a higher prevalence of individuals aged 25 years and older, males, with a current or former intimate partner relationship with the victim, and suspected alcohol use at the time of the aggression. In terms of the characteristics of the aggression, there was a higher prevalence of repeat violence, involving a single aggressor, and occurring in the residence. Conclusions: The notification of interpersonal violence in Espírito Santo showed a high prevalence and was associated with characteristics of the victim, aggressor, and event. This scenario reinforces the need for interventions such as professional qualification, expansion of intersectoral actions, and reformulation of public policies.